Regeneracja krajobrazu po eksploatacji surowców ilastych ceramiki budowlanej w Wielkopolsce = Reclamation of clay open-cast post-mining areas in the Wielkopolska Region - Markuszewska, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Open-cast clay mining causes landscape degradation. During extraction the most negative consequences are the changes of relief, soil and vegetation degradation and land-use changes. On the other hand, excavation brings also positive changes in post-mining landscape. The aim of the present study was to identify changes occurring at clay mining sites, especially worked-out pits.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); krajobraz poeksploatacyjny; eksploatacja surowców ilastych ceramiki budowlanej; bioróżnorodność; georóżnorodność; rekultywacja; sukcesja; Wielkopolska - historia - 18 w.; post-mining landscape; minerals for structural clay products; ex-traction; biodiversity; geodiversity; reclamation; natural succession